PENGAMBILAN KEPUTUSAN DAN PENYELESAIAN MASALAH DALAM KEPEMIMPINAN DI PONDOK PESANTREN AL-MUKHLISIN - Ilmiatus Sa'diyah; Nailil Fitrah (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this study was to analyze decision making and problem solving in leadership at the al-Mukhlisin Islamic boarding school. The research method used in this research is qualitative through interviews and direct observation. All data were obtained directly from the caregiver/head of the al-Mukhlisin Islamic boarding school with careful consideration. The results of this study indicate that the al-Mukhlisin Islamic boarding school in making decisions uses the guideline that a decision should not be taken individually, but also needs input from superiors. In solving the problem, the caretaker of the al-Mukhlisin Islamic boarding school does not immediately give punishment but there are stages that are carried out according to the level of the problem.